Effects of heavy metal-contaminated soils at different levels on rhizosphere microorganisms of Sedum alfredii Hance - LI Ting-qiang; SHU Qin-hong; YANG Xiao-e (浙江大学学报. 农业与生命科学版)
Pot experiments were conducted to study the effects of heavy metal contaminated soils at different levels on soil microbial characteristics of two contrast ecotypes of S. alfredii Hance. The results show that in different soil, populations of bacteria, actinomycetes and fungi and microbial biomass C in rhizospheric soil of S. alfredii Hance were much greater than that in non-rhizospheric one. In slightly polluted soil, there was no significant difference on soil microflora and major microbial physiological groups between the two ecotypes of S. alfredii, whereas in mining soil and seriously polluted soil, populations of bacteria and fungi, physiological groups and microbial biomass C in the rhizospheric soil of the hyperaccumulating ecotype of S. alfredii were much greater than that in non-hyperaccumulating ecotype. The order of soil microorganisms being sensitive to heavy metal pollution was actinomycetes>bacteria>fungus, and nitrobacteria>azotobacteria>ammonifying bacteria > phosphobacteria>cellulose decomposing bacteria. No significant difference on soil base respiration and soil microbial metabolic quotient between the two ecotypes was observed in slightly polluted soil, however, this two indexes in the rhizosphere of non-hyperaccumulating ecotype were much greater than that of hyperaccumulating ecotype in mining soil and seriously polluted soil.